IMPROVING THE INNOVATIVE STRATEGY OF MANAGEMENT OF AGRICULTURAL ENTERPRISES IN THE CONDITIONS OF GLOBALIZATION - Yinhai Miao; Tetiana Kharchenko (Фінансово-кредитна діяльність: проблеми теорії та практики, 2023)
The purpose of the article is to study the peculiarities of the implementation of innovative strategies by Ukrainian farmers, to identify influencing factors, including the influence of global market factors on the effectiveness of the implementation of strategies, and to develop a mathematical approach to assessing the influence of uncertain factors. The methodological basis of the article is the methods and forms of scientific knowledge accepted in science, such as methods: of comparative and abstract-logical analysis, induction and deduction, abstraction, and mathematical formalization. A stratification of the factors of the negative impact of globalization, which slow down the implementation of the innovative strategy and create threats to the activity of agricultural enterprises, is carried out. It is indicated that the main directions of improvement of the innovation strategy should be assessment, consideration, and neutralization of the influence of globalization factors. It is also indicated that this leads to the heterogeneity of the implementation of the innovative management strategy of agricultural enterprises. Prospective directions for the implementation of innovative strategies in agricultural production are stratified. The stages of the implementation of the innovation strategy in the conditions of globalization and the tasks of management for the implementation of the innovation strategy in the global conditions are determined. Peculiarities of the implementation of innovative strategies in Ukraine are revealed. A mathematical model was developed to assess the influence of uncertain global factors, which will allow for reducing risks for the implementation of significant innovative strategies. It is indicated that significant innovative projects could lead to the transformation of agribusiness activities and the need for permanent implementation of innovative processes. It is indicated that thanks to the systemic innovation process, a synthesis of the resource and innovation model of enterprise development could be formed. Taking into account the specifics of innovative strategies and using the developed mathematical approach to assess the influence of uncertain global factors will allow reducing risks in the implementation of innovative strategies and improving their management.